Geographic and socioeconomic factors affecting delivery of bariatric surgery across high‐ and low‐utilization healthcare systems. Issue 7 (4th April 2017) - Doumouras, A. G.; Saleh, F.; Sharma, A. M.; Anvari, S.; Gmora, S.; Anvari, M.; Hong, D.
Abstract: Background: In countries with universal health coverage, the delivery of care should be driven by need. However, other factors, such as proximity to local facilities or neighbourhood socioeconomic status, may be more important. The objective of this study was to evaluate which geographic and socioeconomic factors affect the delivery of bariatric care in Canada. Methods: This was a national retrospective cohort study of all adult patients undergoing bariatric surgery between April 2008 and March 2015 in Canada (excluding Quebec). The main outcome was neighbourhood rate of bariatric surgery per 1000 obese individuals (BMI over 30 kg/m 2 ). Geographic cluster analysis and multilevel ordinal logistic regression were used to identify high‐use clusters, and to evaluate the effect of geographic and socioeconomic factors on care delivery. Results: Having a bariatric facility within the same public health unit as the neighbourhood was associated with a 6·6 times higher odds of being in a bariatric high‐use cluster (odds ratio (OR) 6·60, 95 per cent c.i. 1·90 to 22·88; P = 0·003). This finding was consistent across provinces after adjusting for utilization rates. Neighbourhoods with higher obesity rates were also more likely to be within high‐use clusters (OR per 5 per cent increase: 2·95, 1·54 to 5·66; P = 0·001), whereas neighbourhoods closer to bariatric centres were less likely to be (OR per 50 km: 0·91, 0·82 to 1·00; P = 0·048). Conclusion: In this study, across provincial healthcare systems with high and low utilization, the delivery of care was driven by the presence of local facilities and neighbourhood obesity rates. Increasing distance to bariatric centres substantially influenced care delivery. Abstract : Differences between rural and urban areas